Characteristics and Pattern of Odontogenic Infections with its Treatment Modalities - Sadia Sahibzada, Ajmal Khan, Tariq Sardar, Usama Aurangzeb, Nafeesa Afridi, Intikhab Amanat (Pakistan Journal of Medical & Health Sciences, 2022)
Goal: To identify the characteristics, outcomes and treatment options of odontogenic infections through a retrospective analysis of cases treated for odontogenic abscess. Place and Duration: In the Oral and Maxillofacial department of Cat D Hospital Gara Tajik Peshawar for the duration from June 2021 to November 2021. Methods: A total of 80 patients were included in this study. Age, gender, affected facial spaces, affected teeth, the type of antibiotic therapy, hospital stays, previous medication, past medical history and body temperature during the admission were the studied variables. Results: Patients’ age ranged from 5-85 years, and 42.4% of those who had an odontogenic infection were under 35. Most patients had body temperatures between 37 to 37.5 °C. The mandibular third molars are the most affected teeth. The 7.5% of the mandibular molars were most severely affected among children. 37.5% of patients have 1-44 days stay in hospital. The most often found bacterial strain was streptococci. The commonly involved space was the buccal space, 10 patients have Ludwig’s angina and 48.8% multi-space involvement. Penicillin G with metronidazole or metronidazole and cefazoline were the most often prescribed antibiotic combinations. The 2.5% was the mortality rate and all cases have Ludwig’s angina. Conclusions: The submandibular and buccal spaces are the main affected facial spaces. Penicillin, the most widely used antibiotic, has been proven to be successful in treating infections of the jaw. Odontogenic abscesses are most frequently linked to the eruption of the mandibular molars. Keywords: Abscess, Infection, and Antibiotics